2003
DOI: 10.1128/aem.69.11.6715-6722.2003
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Denitrification ofPseudomonas aeruginosaMonitored by Online NAD(P)H Fluorescence

Abstract: Continuous cultures of Pseudomonas aeruginosa (ATCC 9027) maintained at different dissolved oxygen concentrations (DO) were studied for the effects of DO on various culture properties, especially aerobic respiration and denitrification. The DO was varied from 0 mg/liter (completely anoxic conditions) to 1.3 mg/liter and measured with optical sensors that could accurately determine very low DO based on oxygenquenched luminescence. The strain was found to perform aerobic denitrification; while the specific rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 22 publications
3
63
1
2
Order By: Relevance
“…This is supported by the fact that alginate production and biofilm formation are controlled by oxygen availability in P. aeruginosa (48). Aerobic denitrification in continuous cultures of P. aeruginosa has been demonstrated, even at high concentrations of dissolved oxygen (49). Interestingly, a linkage between the mexEF-oprN (PA2493-PA2495) operon and the nitrate respiratory chain has also been reported, even under aerobic conditions (50).…”
Section: Discussionmentioning
confidence: 57%
“…This is supported by the fact that alginate production and biofilm formation are controlled by oxygen availability in P. aeruginosa (48). Aerobic denitrification in continuous cultures of P. aeruginosa has been demonstrated, even at high concentrations of dissolved oxygen (49). Interestingly, a linkage between the mexEF-oprN (PA2493-PA2495) operon and the nitrate respiratory chain has also been reported, even under aerobic conditions (50).…”
Section: Discussionmentioning
confidence: 57%
“…Freshwater macrophytes (mainly Eicchornia crassipes) are commonly found in the River Cachoeira estuary during the rainy season. Some authors have also reported the ability of bacteria (Thiosphaera pantotropha, Pseudomonas aeruginosa, Pseudomonas stutzeri, Paracoccus denitrificans, Alcaligenes faecalis) to denitrify even in the presence of low levels of dissolved oxygen (BERNAT et al, 2003;CHEN et al, 2003;TAKAYA et al, 2003;JOO et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies (32), no significant changes were observed (Table 1) for most of the genes involved in denitrification (nar, nir, nos, and nor), suggesting that nitrate may induce their expression. This is supported by the capacity of P. aeruginosa for aerobic denitrification (5) and aerobic Nir activity when nitrate is available (1,13). Many denitrification genes are Table B at http://www.urmc.rochester.edu/smd/mbi/bhi/).…”
mentioning
confidence: 93%